PENGARUH BIAYA CORPORATE SOCIAL RESPONSIBILITY (CSR COST) BERDASARKAN MOTIF KEUANGAN, MOTIF ETIKA, DAN MOTIF ALTRUISTIK TERHADAP CORPORATE FINANCIAL PERFORMANCE - Markus Djohan Utama; Devica Pratiwi (Jurnal Akuntansi Bisnis, 2017)
This research aimed to determine the effect of CSR cost that the company paid for community, social, environment, etc. based on financial motive, ethic motive and altruistic motive simultaneously or partial, on the ROE and ROS of company.The research is quantitative research with the help of IBM SPSS Software 21 version with regression analysis. Population of this research is manufactured company listed on the Indonesia Stock Exchange (BEI) in the period 2011-2014. Samples were collected by purposive sampling method and 10 companies are used for this research.The result of the test is CSR cost based on ethic motive have a positive significant effect on ROE and ROS (sig. < 0,05). However, both CSR cost based on financial motive and altruistic motive have no-significant effect on ROE and ROS (sig. > 0,05). For the future research, the researcher recommend that the company which listed on Indonesia Stock Exchange are more transparent and detailed information on the CSR include the activities, the CSR target, the cost that company spend and all the other data about CSR. Then, the company which do the CSR investment and transparent with the CSR report can attract other potential investor for the company, so that can make a positive effect on the financial statement.Keywords: CSR Motive, Financial Motive, Ethic motive, Altruistic Motive